Perceptions of family physicians regarding patients' self-medication - Victoria BABCINETCHI; Alina TIMOTIN; Oleg LOZAN (One Health & Risk Management)
Introduction. Self-medication is the practice of using medications to treat self-diagnosed conditions without prior consultation with a healthcare specialist. This phenomenon is widespread globally, reaching a rate of over 90% in some countries. The objective of the study was to explore and analyze the perceptions of family physicians in the Republic of Moldova regarding self-medication.